Analisis Persepsi Pengguna Aplikasi Lalamove Dengan Menggunakan Metode Technology Acceptance Model (TAM) - Ilman, Zidni Asykar; Saputra, Renaldi; Vikar, Fellissa Azani; Putri, Khalisha Neldia; Ariyanto, Alexsyah Zai (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2024)
A number of on-demand platforms have arisen with the goal of making the delivery of products easier for all members of society, and Lalamove is one of them. Technological improvements have been a big driver in the growth of the logistics business. The study's overarching goal is to investigate users' impressions and thoughts about the Lalamove app via an exploratory lens. To have a better grasp of the topic at hand, this descriptive qualitative study used a content analysis strategy, which entails reducing the amount of data collected. This study's sample was chosen using a non-probability sampling approach, with a focus on user reviews of the Lalamove app located on the Google Play Store marketplace. Based on the TAM, which centres on the two primary components of perceived utility and perceived ease of use, this model attempts to explain why people adopt new technologies. Based on these findings, it seems that the app is still not as user-friendly as it might be. Despite the app's usefulness in enhancing delivery effectiveness, customers still face hurdles such as connecting couriers with users, registration issues, order cancellation, a tracking system that isn't up to par, and payment options that don't fulfil their expectations. Because of this, the Lalamove app's general usefulness and convenience are diminished due to persistent issues.